2009
DOI: 10.2471/blt.08.059212
|View full text |Cite
|
Sign up to set email alerts
|

Control of sexually transmitted infections and prevention of HIV transmission: mending a fractured paradigm

Abstract: Control of sexually transmitted infections (STIs) is feasible, leads to improved sexual and reproductive health and contributes to preventing HIV transmission. The most advanced HIV epidemics have developed under conditions of poor STI control, particularly where ulcerative STIs were prevalent. Several countries that have successfully controlled STIs have documented stabilization or reversal of their HIV epidemics.STI control is a public health outcome measured by reduced incidence and prevalence. The means to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
0
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 39 publications
1
105
0
14
Order By: Relevance
“…Pilot experiments showed that there was no reduction in bacterial viability for up to 4 h in this media. For the labeling experiments, the bacteria were suspended in phosphate-limited RPMI media supplemented with 5% fetal bovine serum (FBS) and KH 2 32 PO 4 (PerkinElmer) (specific activity, 900 to 1,100 mCi/mmol) at 100 Ci/ml. The bacteria were incubated for 3 h, washed, and incubated for an additional 15 min in phosphate-limited RPMI medium.…”
Section: Reverse Transcriptase Pcr (Rt-pcr) and Quantitative Rt-pcr (mentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot experiments showed that there was no reduction in bacterial viability for up to 4 h in this media. For the labeling experiments, the bacteria were suspended in phosphate-limited RPMI media supplemented with 5% fetal bovine serum (FBS) and KH 2 32 PO 4 (PerkinElmer) (specific activity, 900 to 1,100 mCi/mmol) at 100 Ci/ml. The bacteria were incubated for 3 h, washed, and incubated for an additional 15 min in phosphate-limited RPMI medium.…”
Section: Reverse Transcriptase Pcr (Rt-pcr) and Quantitative Rt-pcr (mentioning
confidence: 99%
“…Due to a short duration of infectivity, H. ducreyi can be maintained only in populations with high sex partner change rates, such as commercial sex workers. As a result of syndromic management of genital ulcers, chancroid prevalence has declined in many areas of endemicity and the overall global prevalence of chancroid is now undefined (2). However, reports of chancroid persist from Africa and Asia, implying that these regions have reservoirs of infected sex workers (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Chancroid has a short duration of infectivity and is maintained only in populations with high sex partner change rates, such as commercial sex workers (2). Due to widespread implementation of syndromic management of genital ulcers, the epidemiology of chancroid is poorly defined, but its prevalence has declined in many areas where chancroid formerly was endemic (2). However, reports of chancroid persist from several countries in Africa and Asia, implying that these regions have clinical reservoirs of infected sex workers (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In recent years, however, increasing attention has been given to the importance of structural factors that impact sexual risk behaviours (Aidala et al, 2005;Auerbach, 2009;Evans, Jana, & Lambert, 2010;Lippman et al, 2012;Seeley et al, 2012;Steen, Wi, Kamali, & Ndowa, 2009 (Sumartojo, 2000, p. S3) that are mostly outside of the individual's immediate control (Aidala & Sumartojo, 2007;Blankenship, Friedman, Dworkin, & Mantell, 2006). …”
Section: From Individual To Structural Determinantsmentioning
confidence: 99%
“…In the meantime, it is important to test structural interventions, such as housing, on their effects in reducing sexual risk behaviours, like unprotected sex, by altering the environment from a constraining (Blankenship et al, 2006) to an enabling one (Steen et al, 2009). Based on the accumulated evidence thus far among various homeless populations, several researchers have argued for the potential effect of stable housing and permanent supportive or supported housing on reducing sexual and other risk behaviours associated with HIV, many of which share common risk factors with other STIs (Aidala et al, 2005;Aidala & Sumartojo, 2007;Dickson-Gomez, McAuliffe, Convey, Weeks, & Owczarzak, 2011;Elifson, Sterk, & Theall, 2007;Forney, Lombardo, & Toro, 2007;Kennedy, Wenzel, Brown, Tucker, & Golinelli, 2013;Stein, Nyamathi, & Zane, 2009).…”
Section: Homelessness As a Barrier To Condom Usementioning
confidence: 99%